Analysis of Doctor Service Relationship in the Disease Specialist with Patient Satisfaction in Regional General Hospitals Aceh Tamiang in 2018 - Adrian, M Ali; Gultom, Rumondang (Sari Mutiara Indonesia University Press, 2018)
Good service quality is now important to improve service quality and patient satisfaction. So that satisfied customers will share satisfaction with producers or service providers. Even satisfied customers will share their taste and experience with other customers. This study aims to analyze the relationship between internal medicine specialist services with patient satisfaction in the Aceh Tamiang Regional General Hospital in 2018 to determine the relationship between the quality of service to the professional behavior of doctors in providing health services in accordance with what is expected by patients or families. Indications of the quality of health services that have been received. services ranging from reliability, responsiveness, assurance, empathy and direct evidence to patient satisfaction. The number of populations in the Aceh Taming Regional General Hospital was 423, this research design used a cross-sectional study approach. The population is all inpatients in Aceh Tamiang Hospital. The sample in this study was as many as 80 patients using the accidental sampling technique. Collection of research instruments in the form of questionnaires. Data analysis was tested by chi-square. The conclusion of this study is that there is a significant relationship of tangibles with inpatient satisfaction in Aceh Tamiang Hospital with a value of p = 0.024, There is a significant relationship of reliability with patient satisfaction with p = 0.042, there is a relationship significant responsiveness with patient satisfaction with p = 0.013, there is a significant relationship of assurance (assurance) with patient satisfaction, with a value of p =. 0.024, There is a significant relationship (empathy) with patient satisfaction with a value of p = 0.024